Preservation of table grapes through innovative techniques - Ahmed, Anwaar; Sarwar, Umer; Khalid, Naeem; Abid, Hafiz Muhammad Rizwan; Khalid, Shahmeen; Shibli, Sahar; Malik, Arshad Mahmood (Journal of Pure and Applied Agriculture, 2023)
Worldwide population is increasing day by day due to which the demand for food production will be increased by 60% in 2050. However, a huge portion of food is being lost through pre-harvest and postharvest factors. Grape production is increasing in Pakistan during the recent years. Due to the minimum shelf life, it has significant postharvest losses.